(untitled) - Volti, Rudi (Boulder, 1982)
This book introduce technological development in context. The process of technological development forexample: agricultural technologies, energy technology, surface transportation technologies, medical technologies...
Keywords: Nhà nước và công nghệ,Technology and state; Trung Quốc,China